Astrocyte expression of aging-associated markers positively correlates with neurodegeneration in the frontal lobe of the rhesus macaque brain - Horn, Miranda D.; Forest, Sophia C.; Saied, Ahmad A.; MacLean, Andrew G. (Frontiers in Aging Neuroscience, 2024)
As the population over the age of 65 increases, rates of neurodegenerative disorders and dementias will rise -necessitating further research into the cellular and molecular mechanisms that contribute to brain aging. With the critical importance of astrocytes to neuronal health and functioning, we hypothesized that alterations in astrocyte expression of aging-associated markers p16 INK4a (p16) and sirtuin 1 (SIRT1) with age would correlate with increased rates of neurodegeneration, as measured by FluoroJade C (FJC) staining. To test this hypothesis, 19 rhesus macaques at the Tulane National Primate Research Center were selected based on the following criteria: archival FFPE CNS tissue available to use, no noted neuropathology, and an age range of 5 -30 years. Tissues were cut at 5µm and stained for GFAP, p16, SIRT1, and FJC, followed by whole-slide imaging and HALO® image analysis for percentage of marker-positive cells and relative intensity of each stain. We found the percentage of p16-positive cells increases with age in total cells and astrocytes of the frontal (p = 0.0021, p = 0.0012 respectively) and temporal (p = 0.0226, p = 0.0203 respectively) lobes, as well as the relative intensity of p16 staining (frontal lobe: p = 0.0060; temporal lobe: p = 0.0269). For SIRT1, we found no correlation with age except for an increase in the relative intensity of SIRT1 in the temporal lobe (p = 0.0033). There was an increase in neurodegeneration, as measured by the percentage of FJC-positive cells in the frontal lobe with age (p = 0.0057), as well as in the relative intensity of FJC staining in the frontal (p = 0.0030) and parietal (p = 0.0481) lobes. Importantly, increased p16 and SIRT1 expression in astrocytes correlated with increasing neurodegeneration in the frontal lobe (p = 0.0009, p = 0.0095 respectively). Together, these data suggest that ageassociated alterations in astrocytes contribute to neurodegeneration and provide a target for mechanistic studies in the future.